2016
DOI: 10.1016/j.molmet.2016.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Sex difference in physical activity, energy expenditure and obesity driven by a subpopulation of hypothalamic POMC neurons

Abstract: ObjectiveObesity is one of the primary healthcare challenges of the 21st century. Signals relaying information regarding energy needs are integrated within the brain to influence body weight. Central among these integration nodes are the brain pro-opiomelanocortin (POMC) peptides, perturbations of which disrupt energy balance and promote severe obesity. However, POMC neurons are neurochemically diverse and the crucial source of POMC peptides that regulate energy homeostasis and body weight remains to be fully … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
84
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(96 citation statements)
references
References 30 publications
9
84
0
3
Order By: Relevance
“…Sert Cre mice (from GENSAT) were a generous gift from Dr. Bryan Roth. Htr2c Cre mice were supplied by Dr. Lora Heisler and are described in detail elsewhere7.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sert Cre mice (from GENSAT) were a generous gift from Dr. Bryan Roth. Htr2c Cre mice were supplied by Dr. Lora Heisler and are described in detail elsewhere7.…”
Section: Methodsmentioning
confidence: 99%
“…These results indicate that 5-HT DRN→BNST projections have a predominantly excitatory effect that is dependent on 5-HT 2C R signaling. To examine the role of 5-HT 2C R containing neurons in anxiety-like behavior, we next took advantage of a Htr2c Cre mouse line (Extended Data Figure 3a-b)7. Using Designer Receptors Exclusively Activated by Designer Drugs (DREADDs)8, we found that activation of G q signaling in 5-HT 2C R-expressing neurons in the BNST significantly delayed the onset of feeding in the NSF assay without impacting home cage feeding behavior (Extended Data Figure 3c-g), thus phenocopying the effect observed with 5-HT DRN→BNST fiber stimulation during NSF.…”
mentioning
confidence: 99%
“…Higher obesity among women compared with men in LMICs could be driven by several factors, including sex differences in physiological responses to early-life nutrition, pregnancy-associated weight gain combined with higher parity (40), hormonal signaling related to energy expenditure (16), physical activity levels (144), alcohol consumption (137), depression (79), past and present economic circumstances (19), and sociocultural factors such as the perception of ideal body size and beliefs surrounding acceptability of physical activity in some contexts (68,94). Because maternal obesity is a risk factor for childhood obesity, the increasing obesity prevalence among women of reproductive age could have important intergenerational effects in LMICs (20).…”
Section: Features Of the Obesity Burden In Lmicsmentioning
confidence: 99%
“…Next, we characterized the neurons expressing 5-HT 2C Rs within the VTA and their response to lorcaserin as measured by c-fos immunoreactivity (IR). To investigate the role of VTA 5-HT 2C receptor expressing neurons in the modulation of appetite and the food motivated behavior, we employed a chemogenetic approach (designer receptors exclusively activated by a designer drug, DREADD) (Urban and Roth, 2015) to acutely activate or inhibit this population of neurons using a recently developed 5-HT 2C R CRE mouse line (Burke et al , 2016). These studies identify the therapeutic potential of the activation of a small subset of 5-HT 2C receptor expressing neurons in the reduction of homeostatic feeding and also more broadly in incentive motivation.…”
Section: Introductionmentioning
confidence: 99%